Mood Analysis of Utterances in Indonesia’s Covid-19 Vaccine Article in Online Newspaper - Rahma Yunita Putri; Malikatul Laila (Prasasti: Journal of Linguistics)
This study examines the MOOD analysis of interpersonal meaning in articles in online newspapers about the covid-19 vaccine in Indonesia. The purpose of this study is to explain the formula of MOOD analysis realized in grammar and to describe the speakers' mood in the application of the MOOD analysis in Indonesia's covid-19 vaccine article from online newspaper. The main focus of this research is on descriptive text articles and MOOD structure. This type of research is descriptive qualitative, the author uses observation documentation as a technique to obtain and measure data. The data were obtained by applying the theory of Gerot and Wignell (1994). The researcher found 259 clauses from six texts which became data taken from various online news sources. In the formula, there are various types such as Subject + Finite (Tense), Subject + Finite (Do), Subject + Finite (Modal), Subject + Finite (Have) and Subject + Finite (To be). The most commonly found category is the use of Finite (Tense). In the mood of the speaker, it is found that the speaker expresses certainty, possibility, uncertainty, obligation and advice. What most of the speakers said was certainty. In the analysis also found several categories of modalities, which after that can be included in the degree of modality, namely high, medium, and low. Because the limitations of this study are in a declarative, all clauses are statements that function to convey information from the author to the reader.